Perbedaan Efek Ekstrak Etanol Stevia Dibandingkan Madu Terhadap Perubahan Glukosa Darah Tikus Wistar Model Diabetik - Fatimah R, Siti; ., Kisrini; Puspita Febrinasari, Ratih (Nexus Kedokteran Translasional, 2012)
Background:Steviaâs leaf contains steviol, stevioside and rebaudioside which have effect to increase secretion insulin. Honey, natural sweetener contains several antioxidant such as propolis, flavonoid and vitamin. It will eliminate free radicals and indirectly improve pankreas glands cells to produce insulin. This research was aimed to know the difference effect of steviaâs ethanol extract comparedto honey on changing of blood glucoselevel on diabetic model Wistar rats. Methods:This was experimental research with pre and post test controlled group design. Samples were 32 male rats, Wistar Strain, 6-8 weeks and + 200 gweight. Sampling technique used in this research was incidental sampling. Samples were divided into 4 groups: negative control group (aquadest), positive control (glibenclamide dose 0.09 mg/200 g body weight), treatment group 1 (steviaâs ethanol extract dose 20 mg/200 g body weight), treatment group 2 (honey dose 2 ml/200 g body weight). Data were analyze using Saphiro-Wilkâs test of normality and Friedmann test (Î± = 0.05) and Post Hoc Multiple Comparison (Wilcoxon) (Î± = 0.05) using SPSS 17 for Windows. Results:There was a significant difference (p = 0.002) on the Wistarâs blood glucose level which was given steviaâs ethanol extract or honey. Steviaâs ethanol extract effect more on decreasing the blood glucose than honey. But, the both of them are able to decrease the Wistarâs blood glucose on diabetic model Conclusions:Steviaâs ethanol extract has the effect of decreasing blood glucose level on diabetic model Wistar rats better than honey. Keywords:ethanol extract of stevia, honey, alloxan, changes in blood glucose levels.